Community perceptions toward economic and environmental impacts of tourism on local communities - Aref, Fariborz; Redzuan, Ma'rof; Gill, Sarjit S. (Canadian Center of Science and Education, 2009)
This paper investigates the community perceptions toward economic and environmental impacts of tourism in Shiraz, Iran. Special focus is on the differences in perceptions between the Old and New Districts of Shiraz. The study demonstrates that there are broadly similar views among the community leaders and community residents from both districts of Shiraz. In fact, a high percentage of the answers obtained highlighted positive aspects environmental and economic impacts of tourism toward local communities. According to the survey, the strongest and favourable perceptions toward tourism impacts are found to be linked with environmental aspects and while economic matters are found to be the least favourable in terms of the perceived impacts on tourism. T-test analysis of the study indicates that there is no significant difference between community leaders' perceptions in both districts of Shiraz City. Results drew from discussion with the target group show that the community residents have positive perceptions toward economic and environmental impacts of tourism with only minor differences with each other.